GO Shaping of Omnidirectional Dual-Reflector Antennas with Arbitrary Main-Beam Direction in Elevation Plane by Connecting Conic Sections - Penchel, Rafael A. [UNESP]; Zang, Sandro R.; Bergmann, Jose R.; Moreira, Fernando J. S. (Hindawi Ltd, 2018)
This work discusses an alternative geometrical optics (GO) technique to synthesize omnidirectional dual-reflector antennas with uniform aperture phase distribution together with an arbitrary main-beam direction for the antenna radiation pattern. Sub- and main reflectors are bodies of revolution generated by shaped curves defined by local conic sections consecutively concatenated. The shaping formulation is derived for configurations like ADC (axis-displaced Cassegrain) and ADE (axis-displaced ellipse) omnidirectional antennas. As case studies, two configurations fed by a TEM coaxial horn are designed and analyzed by a hybrid technique based on mode matching and method of moments in order to validate the GO shaping procedure.